R/V NATSUSHIMA NT97-11 Cruise Data - JAMSTEC (JAMSTEC, 1997)
[CRUISE DATA] This site includes a cruise dataset acquired in NT97-11 on R/V NATSUSHIMA from 1997-06-27 to 1997-07-06.
Observation contents: Rock Sample, Biological Sample
Keywords: Research cruise; R/V NATSUSHIMA; oceans